Profiling Indonesian Medical Tourists: A Motivation-Based Segmentation Study - Jeanny Angela; Ivan Budi Suryono; Serli Wijaya (Universitas Hayam Wuruk Perbanas, 2020)
In the past few decades, the number of Indonesians who travel abroad for medicaltourism has increased dramatically. A literature review has indicated that researchinvestigating the underlying motivational factors for Indonesians to travel overseasfor medical treatment is still a few. Therefore, this study aimed to segment theIndonesian medical tourists based on push and pull travel motivation constructs.Exploratory factor analysis and cluster analysis techniques were applied to analyzethe data. A survey was completed to 192 Indonesians who have had a medical travel experience overseas. The results of this study revealed four push motivational factors and three pull motivational factors. Based on this push and pull factors, three different medical tourist segments were identified: trendy, prudent, and opportunistic segments. The emergence of these three segments would require different approaches and strategies for tourism stakeholders to serve each segment better.